(untitled) (African Journal of Dairy Farming and Milk Production, 2013)
Due to the nature and strategic importance of agriculture, governments in whole world somehow support agricultural sector. This sector plays an important role in Turkish economy despite the share of industry and services are rising constantly. The sector has basic structural problems such as poor mechanization, small farm size and uncoordinated and unplanned agricultural production. Although Turkey has developed substantial agricultural policy reforms, particularly in animal husbandry sector, to be in line with European Union and World Trade Organization regulations, there are a lot to do to improve the sector. One of the most important aspects of the agricultural supports is to distribute them efficiently and in an equitable way to the sector. This study aims to explore the factors affecting the dairy farmers’ utilization of agricultural supports using ordered probit approach. For this end, survey data were used and the results showed that education level, form of farming, breed and roughage usage variables were good predictors of dairy farmers’ utilization of agricultural supports. Therefore, in order to have an efficient and equitable agricultural support policy, education level of the farmers can be increased and farmers can be induced to have a more market-oriented production and culture breeds.